Emergy Synthesis of Food Preparation and Diets in the “Green” Urban District Rosendal, in Uppsala, Sweden - Maassen, Jacinda J.; Rydberg, Torbjörn; Bergquist, Daniel (Journal of Environmental Accounting and Management, 2026)
Urban populations typically consume large quantities of food and foods with high resource demands. To better understand the environmental support behind the food preparation and diets of a “green” urban district, this study evaluates the resource support and sustainability of three diet scenarios in Rosendal, Uppsala, Sweden using emergy synthesis. Scenario one represents actual food preparation and the average diet including meat consumption in Rosendal from Maassen (2017). Two hypothetical scenarios, a vegetarian and pescatarian diet, are examined to investigate the potential implications of different diets on environmental support and total emergy. The results show that the total emergy is lower for the vegetarian and pescatarian scenarios in comparison to the diet including meat, but the ratios and indices for all three diets are not significantly different. The ratios and indices indicate the food preparation and diet system in Rosendal is a consumer and high throughput system that is not sustainable or efficient, mainly due to strong reliance on imported and to a high degree nonrenewable inputs. The results also show that the typical resident, no matter the diet, overshoots the solar share strictly based on their food preparation and consumption alone. This indicates that the specific diet is not as significant as to where and how the food is produced, processed, packaged and delivered from farm to fork. Therefore, this study concludes that specific dietary changes may not be the main issue when considering the sustainability of food consumption in urban populations, but rather the next larger system from which the food is obtained. To improve the efficiency and sustainability of urban food preparation and diets, food should be considered from a holistic perspective that considers environmental performance and resource support in the larger scale systems from where food is sourced and food production should be integrated into urban planning policies.